Indiana’s Formula Revisions and Bonner v. Daniels: An Analysis of Equity and Implications for School Funding - Marilyn Hirth; Edward Eiler (Educational Considerations, 2012)
Indiana has a long history of school funding issues and distribution formula revisions. The most recent modifications to the formula were made between 2005 and 2009.
Keywords: foundation; formula; distribution; school; finance; Indiana; litigation; states; court; implications; Bonner v. Daniels; funding; equity